OPINION OF YOUTH ON ISSUES AND CHALLENGES RELATED TO EMPLOYMENT: A STUDY IN MYSORE CITY - A.K, Mohan (International Journal of Research -GRANTHAALAYAH, 2016)
Employment status is one of the developmental indicators of nation. For this two things are vital, one is availability of employment opportunities and second is skillful workforce. Employment and skills are linked with many other social, economic and demographic factors. India is hoping to excel economically using its youth power. Hence many skill development programmes linked with employment options are being provided to youth by government and non-government agencies. However, the issue of employment moved from unemployment to under employment. This paper highlighted the challenges faced by urban youth and their issues and expectations with regard to employment. The study also tried to understand the trend of employment and to suggest necessary modifications in skills training based on the opinion provided by youth.